2015
DOI: 10.1088/0004-637x/799/2/180
|View full text |Cite
|
Sign up to set email alerts
|

A STATISTICAL RECONSTRUCTION OF THE PLANET POPULATION AROUNDKEPLERSOLAR-TYPE STARS

Abstract: Using the cumulative catalog of planets detected by the NASA Kepler mission, we reconstruct the intrinsic occurrence of Earth-to Neptune-size (1 -4R ⊕ ) planets and their distributions with radius and orbital period. We analyze 76,711 solar-type (0.8 < R * /R ⊙ < 1.2) stars with 430 planets on 20-200 d orbits, excluding close-in planets that may have been affected by the proximity to the host star. Our analysis considers errors in planet radii and includes an "iterative simulation" technique that does not bin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 65 publications
(102 reference statements)
9
122
1
1
Order By: Relevance
“…Recent studies (Youdin 2011;Fressin et al 2013;Petigura et al 2013;Weiss & Marcy 2014;Marcy et al 2014;Silburt et al 2015;Rogers 2015) have shown that the size distribution of extrasolar planets peaks at about ∼2 Earth radii (between 1.5 and <3.0). This same pattern is clearly present in the current planet candidate population (Burke et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Youdin 2011;Fressin et al 2013;Petigura et al 2013;Weiss & Marcy 2014;Marcy et al 2014;Silburt et al 2015;Rogers 2015) have shown that the size distribution of extrasolar planets peaks at about ∼2 Earth radii (between 1.5 and <3.0). This same pattern is clearly present in the current planet candidate population (Burke et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…All red (r − J > 2.2) stars were classified as dwarf or giant stars based on available spectra and photometry. The intrinsic, de-biased planet population with orbital period P < 180 d was constructed using the method of iterative Monte Carlo (Cappe et al 2007), where a synthetic input population of planets is evolved by repeated passage through a detection simulation (Silburt et al 2015). Host stars and planets are randomized with the assumption that, within the sample, their properties are uncorrelated.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the small fraction of stars with warm debris disks, rocky planets within 1 AU appear to be fairly common companions to solar-type stars (Youdin 2011b;Fang & Margot 2012;Batalha et al 2013;Foreman-Mackey et al 2014;Silburt et al 2015;Winn & Fabrycky 2015). Although the false positive rate is uncertain, recent attempts to confirm Kepler candidates with ground-based and other space-based observations suggest false positive rates ranging from ∼ 10% to 75% for various ranges of planet masses (e.g., Morton & Johnson 2011;Santerne et al 2012;Fressin et al 2013;Sliski & Kipping 2014;Désert et al 2015;Colón et al 2015;Santerne et al 2016;Coughlin et al 2016;Mullally et al 2016;Morton et al 2016).…”
Section: Earth Mass Planets At 025-1 Au Are Fairly Commonmentioning
confidence: 99%